Comparative education in an age of competition and collaboration. Issue 1 (2nd January 2020) - Powell, Justin J. W.
ABSTRACT: Comparative education relies on experiences, expertise, data, and criticism derived from multiple contexts and diverse levels to generate insights, facilitate understanding, and explain change. Marked by connectivity, our contemporary era vastly increases the (potential) diffusion of ideas essential for scientific advance. Three interlocking trends emphasise the growing relevance of comparative educational research. Firstly, competition has become more potent – among scholars, their organisations, and within as across countries. Secondly, educational studies, as science more generally, are increasingly conducted in collaboration – across disciplinary, cultural, linguistic, and organisational boundaries – enhancing the potential for discovery while producing influential scholarship. Thirdly, while educational research and policymaking are increasingly comparative, comparative knowledge stores are often only selectively used. To counter such reductionism, in-depth comparative institutional analysis across divides of academy, politics, and practice remain crucial. The multidisciplinary field must claim its relevance more persuasively, even as scholarly exchange, mobilities, and cultural knowledge endure as vital foundations.